1987
DOI: 10.1002/ana.410210108
|View full text |Cite
|
Sign up to set email alerts
|

GABA‐mimetic drugs enhance apomorphine‐induced contralateral turning in rats with unilateral nigrostriatal dopamine denervation: Implications for the therapy of Parkinson's disease

Abstract: The underlying mechanisms responsible for advanced Parkinson's disease's becoming refractory to dopamimetic therapies are unclear. Postmortem brain studies indicate that patients with Parkinson's disease have decreased basal ganglia gamma-aminobutyric acid (GABA) function in addition to profound striatal dopamine (DA) deficiencies. In experimental animals, GABA-utilizing striatal and nigral projection neurons appear to mediate motor behaviors arising from the stimulation of striatal DA receptors by agonists. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In the late 1980s, some opinion leaders in the field of movement disorders [ 9 ] had suggested that drugs that may specifically enhance GABAergic neurotransmission may be potentially helpful in the treatment of PD, but at that time there was scanty evidence supporting this intriguing hypothesis. In particular, a pilot study had suggested that GABA agonists such as progabide [ 10 ] might be helpful in the treatment of motor symptoms of patients with PD, in agreement with an experimental study in rats showing the effects of progabide [ 11 ] on motor function (turning behaviour) and with previous postmortem findings showing abnormalities in the GABAergic systems of the brain of patients with Parkinson's disease [ 12 ].…”
Section: Potential Beneficial Effects Of Zolpidem a Positive Allosupporting
confidence: 71%
“…In the late 1980s, some opinion leaders in the field of movement disorders [ 9 ] had suggested that drugs that may specifically enhance GABAergic neurotransmission may be potentially helpful in the treatment of PD, but at that time there was scanty evidence supporting this intriguing hypothesis. In particular, a pilot study had suggested that GABA agonists such as progabide [ 10 ] might be helpful in the treatment of motor symptoms of patients with PD, in agreement with an experimental study in rats showing the effects of progabide [ 11 ] on motor function (turning behaviour) and with previous postmortem findings showing abnormalities in the GABAergic systems of the brain of patients with Parkinson's disease [ 12 ].…”
Section: Potential Beneficial Effects Of Zolpidem a Positive Allosupporting
confidence: 71%